Effect of T-stress on Fracture of a Long Cracked Plate in Unsteady Heat Transfer. (13th November 2021) - Zhou, Shaoqing; Li, Limin
Abstract : In order to accurately predict the structure fracture caused by thermal load, a modified maximum tensile stress (MTS) criterion combined with T -stress is proposed. The modified MTS uses a two-parameter model (stress intensity factor K and T -stress) to describe the fracture behavior under thermal load. The T -stress and stress intensity factor at the crack tip are solved by using J-integral in the theoretical calculation of a cracked strip with temperature difference. The results show that T -stress can affect the fracture toughness and the stress at the crack tip of the cracked strip with temperature difference. This provides a basis for the simulation of structural fracture under thermal load.